Evaluation of interseeded grain sorghum and soybeans as a silage crop - L.H. Harbers; K.K. Bolsen; H. Hartadi (Kansas Agricultural Experiment Station Research Reports, 1992)
Dry matter yield of grain sorghum alone averaged more than 1.0 ton per acre higher than that of intercropped grain sorghum-soybeans in both 1988 and 1989. All silage yields were lower in 1989 because of drought. Grain sorghum silage had less NDF and ADF, but intercropped silages had over 4 percentage units more crude protein. Digestibility coefficients for crude protein, NDF, and ADF tended to favor intercropped silages, but yearling steer performance favored grain sorghum silage. Studies over 4 years (1986 to 1989) suggest that intercropping might be more beneficial for dairy cattle producers than beef producers.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Grain sorghum; Soybeans; Intercrop; Silage